Cascadable First-Order and Second-Order Inverse Filters Based on Second-Generation Voltage Conveyors - Roongmuanpha, Natchanai; Likhitkitwoerakul, Nutcha; Pukkalanun, Tattaya; Faseehuddin, Mohammad; Tangsrirat, Worapong (My University, 2025)
This study introduces four novel configurations of first-order and second-order multifunction inverse filters in both voltage-mode (VM) and current-mode (CM) using second-generation voltage conveyors (VCIIs). The first-order VM and CM inverse filters utilize only three passive components together with one VCII for VM and two VCIIs for CM realizations, which can provide lowpass and highpass inverse filter responses. The latter, second-order VM and CM multifunction inverse filters, can be constructed using the corresponding first-order inverse filters as their core circuits. These filters offer all the basic inverse filter functions, including lowpass, bandpass, and highpass inverse responses with all gains obtained from the same design. All the inverse filter realizations are cascadable. No component matching requirements are necessary for all filter responses. The non-ideal effects of the VCII on the performance of the proposed inverse filters are thoroughly examined. To prove the feasibility of the designs, the PSPICE program performed several simulations, utilizing model parameters of 0.18 µm CMOS technology. Some testing experiments were conducted using the commercially available IC-type AD844s for evaluating the practical performance of the designed inverse filters.
Keywords: current-mode circuit; first-order filter; inverse filter; second-generation voltage conveyor (VCII); second-order filter; voltage-mode circuit